A Council of Europe Perspective on the European Union’s Accession to the European Convention on Human Rights - Jörg Polakiewicz; Irene Suominen-Picht (European Papers)
(Series Information) European Papers - A Journal on Law and Integration, 2024 9(2), 729-744 | Article | (Table of Contents) I. Introduction. – II. Guiding principles. – III. Proceedings before the European Court of Human Rights. – III.1. The co-respondent mechanism. – III.2. The “prior involvement” of the Court of Justice. – III.3. Operation of inter-party applications and ECHR advisory opinions. – III.4. The principle of mutual trust between EU Member States and relationship between the two articles 53. – IV. Participation of the EU in the Committee of Ministers. – V. Election of judges. – VI. Conclusion. | (Abstract) The Article discusses the European Union’s accession to the European Convention on Human Rights (ECHR) from the Council of Europe’s perspective, focusing on the renegotiations between June 2020 and March 2023, which led to 10–20 formal amendments to the Draft Accession Agreement (DAA). It examines whether the guiding principles agreed upon in 2010 have been upheld and addresses the EU’s accession in terms of the co-respondent mechanism, the principle of mutual trust, and the EU’s participation in the Committee of Ministers, among other aspects. The document emphasises the balance between respecting the EU’s constitutional requirements and maintaining the integrity of the Convention system, concluding that the revised DAA represents a collaborative effort to address the challenges posed by the Court of Justice of the European Union’s (CJEU) Opinion 2/13 and to ensure coherent human rights protection in Europe.